Gastrointestinal disorders and intestinal bacteria: Advances in research and applications in therapy - Ohkusa, Toshifumi; Nishikawa, Yuriko; Sato, Nobuhiro (Frontiers in Medicine, 2023)
Intestinal bacteria coexist with humans and play a role in suppressing the invasion of pathogens, producing short-chain fatty acids, producing vitamins and controlling the immune system. Studies have been carried out on culturable bacterial species using bacterial culture methods for many years. However, as metagenome analysis of bacterial genes has been developed since the 1990s, it has recently been revealed that many bacteria in the intestine cannot be cultured and that approximately 1,000 species and 40 trillion bacteria are present in the gut microbiota. Furthermore, the composition of the microbiota is different in each disease state compared with the healthy state, and dysbiosis has received much attention as a cause of various diseases. Regarding gastrointestinal diseases, dysbiosis has been reported to be involved in inflammatory bowel disease, irritable bowel syndrome and nonalcoholic steatohepatitis. Recent findings have also suggested that dysbiosis is involved in colon cancer, liver cancer, pancreatic cancer, esophageal cancer and so on. This review focuses on the relationship between the gut microbiota and gastrointestinal/hepatobiliary diseases, and new therapies targeting the gut microbiota are also discussed.